Ni-plated steel sheet and method for producing the same

By adopting the power-on mode and annealing treatment with no fixed current density in the Ni plating process of Ni steel plate, suitable Fe-Ni diffusion alloy area and Ni plating area are formed, and the processability and Ni dissolution resistance of Ni plating steel plate are solved. The Ni-plated steel plate with high formability and Ni dissolution resistance is achieved, and is suitable for battery steel plates.

CN113195795BActive Publication Date: 2025-01-07NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980085007.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-27
Filing Date
2019-12-20
Publication Date
2025-01-07
Estimated Expiration
2039-12-20

AI Technical Summary

Technical Problem

The conventional Ni-plated steel plate is difficult to balance the processability and Ni dissolution resistance, and it is difficult to provide the required formability and excellent Ni dissolution resistance of the steel plate for battery.

Method used

In the Ni plating process of Ni steel plate plate, the power-on mode is adopted with an unfixed current density, including three or more power-on periods and rest periods, and the heat-on temperature is set to be 650°C or more and 850°C or less during the annealing process, and the heat-on temperature is set to be 650°C or less. The time is 10 seconds or less than 109 seconds, and the Fe-Ni diffusion alloy region and the Ni plating region are formed, and the average equivalent circle diameter of the Ni (fcc) grains in the Ni plating region are controlled to be within the range of 0.2 to 4.0 μm.

Benefits of technology

The high forming properties and extremely high Ni dissolution resistance of Ni plated steel plates are achieved, and the processability and corrosion resistance of the steel plates for batteries are ensured, while reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113195795B_ABST
    Figure CN113195795B_ABST
Patent Text Reader

Abstract

A Ni-plated steel plate according to one embodiment of the present invention comprises a base steel plate, an Fe-Ni diffusion alloy region and a Ni-plated region, wherein the Fe-Ni diffusion alloy region is arranged on the base steel plate, and the Ni-plated region is arranged on the Fe-Ni diffusion alloy region, and an average equivalent circle diameter of grains composed of Ni (fcc) in the Ni-plated region measured in a cross section perpendicular to a rolled surface of the base steel plate is 0.2 to 4.0 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a Ni-plated steel sheet and a method for producing the Ni-plated steel sheet.

[0002] This application claims priority based on Japanese Patent Application No. 2018-245984 filed in Japan on December 27, 2018, the contents of which are incorporated herein by reference. Background Art

[0003] Since Ni-plated steel sheets have high chemical stability, they are preferred as materials for battery cans. However, in view of the application to xEVs (a general term for EVs, hybrid vehicles, and plug-in hybrid vehicles), Ni-plated steel sheets need to have high chemical stability for a longer period of time.

[0004] In recent years, the demand for miniaturization, high capacity and long-term durability of batteries has increased. Therefore, the processability and long-term durability required for battery steel plates have become increasingly higher. However, there is an inverse relationship between processability and chemical stability (specifically, resistance to Ni dissolution). Generally, it is possible to make the Ni plating difficult to crack and improve processability by miniaturizing the grains that constitute the Ni plating. However, when the grains are miniaturized, the amount (area) of the grain boundary, which is the starting point of Ni dissolution, increases, thereby impairing Ni dissolution resistance.

[0005] As a steel sheet for a battery, for example, the following steel sheets have been proposed.

[0006] Patent document 1 discloses a surface-treated steel plate for a battery container, comprising a steel plate, an iron-nickel diffusion layer and a nickel layer, wherein the iron-nickel diffusion layer is formed on the steel plate, and the nickel layer is formed on the iron-nickel diffusion layer to constitute the outermost layer; in the surface-treated steel plate for a battery container, when the Fe intensity and the Ni intensity are continuously measured from the surface of the surface-treated steel plate for a battery container in the depth direction using a high-frequency glow discharge emission spectrophotometer, the difference (D2-D1) between the depth (D1) at which the Fe intensity represents a first predetermined value and the depth (D2) at which the Ni intensity represents a second predetermined value, i.e., the thickness of the iron-nickel diffusion layer is 0.04 to 0.31 μm, and the total amount of nickel contained in the iron-nickel diffusion layer and the nickel layer is 4.4 g / m 2 Above and less than 10.8g / m 2 .

[0007] Patent document 2 discloses a Ni-plated steel sheet with excellent stamping formability, which has an Fe-Ni diffusion layer and a Ni layer softened thereon on the surface corresponding to the outer surface of the battery can, and also has a semi-glossy Ni-plated layer thereon, and the Ni adhesion amount of the Fe-Ni diffusion layer and the Ni layer softened thereon is less than the adhesion amount of the semi-glossy Ni-plated layer, and the average roughness Ra of the semi-glossy Ni layer measured by a stylus roughness meter is 1.0 μm to 2.0 μm, and the maximum height Ry is 5 μm to 20 μm. Similarly, in Patent document 2, the Ni adhesion amount of the Fe-Ni diffusion layer and the Ni layer softened thereon is 5 to 8 g / m 2 , the adhesion of semi-gloss Ni plating layer is 8g / m 2 Furthermore, a Ni-plated steel sheet having a semi-glossy plating layer and excellent press formability is disclosed, wherein the surface roughness Ra' of the semi-glossy Ni-plating layer within 2.5 μm×2.5 μm measured by an atomic force microscope is between 5 and 22 nm.

[0008] Patent document 3 discloses a Ni-plated steel sheet for battery cans having excellent stamping properties, characterized in that it has an Fe-Ni diffusion layer and a Ni layer thereon on a surface corresponding to the outer surface of the battery can, and also has a semi-glossy Ni-plated layer thereon, and the Ni adhesion amount of the Fe-Ni diffusion layer and the Ni layer thereon is less than the adhesion amount of the semi-glossy Ni-plated layer, and the adhesion amount of the semi-glossy Ni-plated layer is 2.25 g / m 2 As mentioned above, for the surface of the semi-gloss Ni plating layer, the surface roughness Ra1 within the range of 2.5μm×2.5μm obtained by atomic force microscopy is between 3 and 11nm, and among the surface roughness Ra of the semi-gloss Ni plating layer, the surface roughness Ra2 obtained by a stylus roughness meter is greater than 0.3μm and less than 2.0μm.

[0009] Patent document 4 discloses a method for manufacturing a Ni-plated steel sheet, which comprises the steps of plating the steel sheet surface with Ni in an amount of 0.3 to 2 μm per unit area weight of Ni, heating the Ni-plated steel sheet to 600 to 800°C to form an Fe-Ni diffusion layer on the outermost layer, and performing surface smooth rolling on the steel sheet, so that the roughness Ra of the Fe-Ni diffusion layer is 0.9 to 2.0 μm and the roughness Ry is 4.0 to 15 μm. Furthermore, Patent document 4 discloses that an aqueous solution containing a water-soluble emulsion is used as a stamping lubricant to perform deep drawing on the Ni-plated steel sheet to form a battery can, wherein the Ni-plated steel sheet has an Fe-Ni diffusion layer on the outermost layer, the roughness Ra of the diffusion layer is 0.9 to 2.0 μm, the roughness Ry is 4.0 to 15 μm, and the ratio of Fe to Ni in the diffusion layer is 20 to 50% based on analysis based on the Auger method.

[0010] Patent document 5 discloses a highly corrosion-resistant nickel-plated steel strip, wherein a nickel-plated layer is formed on one or both sides of a cold-rolled steel sheet, a portion or all of the nickel-plated layer forms a nickel-iron diffusion layer, and the exposed proportion of iron in the outermost surface of the nickel-plated layer is less than 30%.

[0011] However, even with the above-mentioned techniques, it is difficult to provide a Ni-plated steel sheet having the formability required for a steel sheet for a battery and excellent Ni dissolution resistance.

[0012] Prior art literature

[0013] Patent Literature

[0014] Patent Document 1: International Publication No. 2017 / 094919

[0015] Patent Document 2: International Publication No. 2011 / 024443

[0016] Patent Document 3: International Publication No. 2011 / 083562

[0017] Patent Document 4: International Publication No. 2010 / 143374

[0018] Patent Document 5: Japanese Patent Application Publication No. 6-2104 Summary of the invention

[0019] Technical problem to be solved by the invention

[0020] An object of the present invention is to provide a Ni-plated steel sheet having the formability required for a steel sheet for a battery and excellent resistance to Ni dissolution, and a method for producing the same.

[0021] Technical means for solving technical problems

[0022] The gist of the present invention is as follows.

[0023] (1) A Ni-plated steel sheet according to one embodiment of the present invention comprises a base steel sheet, an Fe-Ni diffusion alloy region and a Ni-plated region, wherein the Fe-Ni diffusion alloy region is arranged on the base steel sheet, and the Ni-plated region is arranged on the Fe-Ni diffusion alloy region, and an average equivalent circle diameter of grains composed of Ni (fcc) in the Ni-plated region measured in a cross section perpendicular to a rolled surface of the base steel sheet is 0.2 to 4.0 μm.

[0024] (2) In the Ni-plated steel sheet described in (1) above, a value obtained by dividing the average equivalent circle diameter of the crystal grains composed of the Ni (fcc) in the Ni-plated region by the thickness of the Ni-plated region may be 0.50 to 2.00.

[0025] (3) In the Ni-plated steel sheet described in (1) or (2), the Ni deposition amount per single surface in the Fe-Ni diffusion alloy region and the Ni-plated region may be 1.5 to 65 g / m 2 .

[0026] (4) A method for manufacturing a Ni-plated steel sheet according to another embodiment of the present invention is a method for manufacturing a Ni-plated steel sheet according to any one of (1) to (3) above, comprising a step of electroplating Ni on a base steel sheet to obtain a raw Ni-plated steel sheet, and a step of annealing the raw Ni-plated steel sheet, wherein the Ni electroplating includes three or more power-on periods and rest periods between the power-on periods, and the average current density per single surface of the base steel sheet during each of the power-on periods is set to 200 A / m 2 ~3500A / m 2 The current flow rate per single side of the base steel plate during each current flow period is set to 800 C / m 2 ~40000C / m 2 During the energization period, the current density is set to be non-fixed, and the maximum current density of each single side of the base steel plate is set to be 7% or more higher than the average current density of each single side of the base steel plate, and 4000A / m 2 Hereinafter, the soaking temperature in the annealing is set to be 650° C. or higher and 850° C. or lower, and the soaking time in the annealing is set to be 10 seconds or higher and 109 seconds or lower.

[0027] (5) In the method for producing a Ni-plated steel sheet described in (4) above, each of the idle periods may have a length of 0.1 seconds or more.

[0028] Effects of the Invention

[0029] According to the present invention, it is possible to provide a Ni-plated steel sheet having the formability required for a steel sheet for a battery and having excellent resistance to Ni dissolution, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] FIG. 1-1 is an example of a current conduction pattern in a Ni electroplating step in the method for producing a Ni-plated steel sheet according to the present embodiment.

[0031] Picture 1-2 This is an example of a current-conducting pattern in the Ni electroplating step in the method for producing a Ni-plated steel sheet according to the present embodiment.

[0032] Picture 1-3 This is an example of a current-conducting pattern in the Ni electroplating step in the method for producing a Ni-plated steel sheet according to the present embodiment.

[0033] Picture 2 It is a schematic diagram of the Ni-plated steel sheet of this embodiment.

[0034] Picture 3 This is an example of an EBSP image of the Ni-plated region of the Ni-plated steel sheet according to the present embodiment. DETAILED DESCRIPTION

[0035] The present inventors have studied the effects of various manufacturing conditions in order to improve the Ni dissolution resistance without damaging the formability of the Ni-plated steel sheet. As a result, it was found that the Ni dissolution resistance can be dramatically improved without damaging the formability of the Ni-plated steel sheet by making the power-on mode in the Ni electroplating process meet the requirements described below.

[0036] FIG. 1-1 is a schematic diagram showing an example of a power-on mode in a Ni electroplating process discovered by the present inventors, wherein the vertical axis is current density and the horizontal axis is time. The power-on mode satisfies the following requirements. In addition, the so-called setting of the current density to be non-fixed means that, as shown in FIG. 1-1, the current density is not set to a fixed value during the power-on period.

[0037] (1) It includes three or more energization periods and rest periods between these energization periods.

[0038] (2) The average current density I during each power-on period ave Set to 200~3500A / m 2 .

[0039] (3) The amount of current applied during each current application period is set to 800 to 40,000 C / m 2 .

[0040] (4) The current density in each energization period is set to be non-constant, and the maximum current density I is set to max The average current density I during the power-on period ave More than 7% larger.

[0041] The Ni-plated steel sheet obtained through the Ni electroplating process with the power-on mode satisfying the above requirements and the annealing process satisfies the formability required for battery steel sheets and shows extremely high resistance to Ni dissolution. In order to study the reasons why the Ni-plated steel sheet has both high formability and high resistance to Ni dissolution, the structure of the Ni-plated area was analyzed. As a result, the average equivalent circle diameter of the grains in the Ni-plated area observed in the cross section perpendicular to the rolling surface of the base steel plate 11 (hereinafter sometimes referred to as "cross section") is in the range of 0.2 to 4.0 μm. This means that the coarsening of the grains is suppressed to a degree that can suppress the progress of cracks, and the amount (area) of the Ni dissolution corrosion path, i.e., the grain boundary, is reduced inside the Ni-plated area.

[0042] In addition, the grain size evaluation of the crystal grains in the Ni-plated region is usually implemented in the coating surface (i.e., the surface parallel to the rolling surface of the parent steel plate). However, in order to evaluate the amount of the grain boundary included in the Ni-plated region, it is necessary to measure the grain size in the cross section of the Ni-plated region (i.e., the cross section perpendicular to the rolling surface of the parent steel plate). In addition, the present inventors have conducted an investigation, and the average equivalent circular diameter of the crystal grains measured in the surface of the Ni-plated region and the average equivalent circular diameter of the crystal grains measured in the cross section of the Ni-plated region are not found to be related. Because the crystallization of the Ni-plated region constituting the Ni-plated steel plate is not equiaxed grains, the average equivalent circular diameter of the Ni (fcc) crystal grains measured in the surface of the Ni-plated region is not necessarily consistent with that measured in the cross section of the Ni-plated region. Therefore, it is considered that the average equivalent circular diameter of the crystal grains measured in the surface of the Ni-plated region is used as a substitute index for the grain size measured in the cross section of the Ni-plated region is inappropriate. Therefore, the present inventors decide to control the average equivalent circular diameter of the crystal grains measured in the cross section of the Ni-plated region.

[0043] The reason why the above-mentioned energization mode gives such a coating structure to the Ni-plated area is not clear. The present inventors have predicted the existence of the following mechanism at the current point in time. In the Ni electroplating process according to the above-mentioned energization mode, the electrodeposition stress can change periodically. The thus obtained Ni plating is considered to have a periodic internal stress change along the depth direction. This internal stress change is presumed to have caused a certain influence on the Ni-plated area during annealing.

[0044] The Ni-plated steel sheet 1 of this embodiment obtained based on the above findings is as follows Picture 2 As shown, it includes a base steel plate 11, a Fe-Ni diffusion alloy region 12 and a Ni-plated region 13, wherein the Fe-Ni diffusion alloy region 12 is arranged on the base steel plate 11, and the Ni-plated region 13 is arranged on the Fe-Ni diffusion alloy region, and the average equivalent circle diameter of the Ni (fcc) grains in the Ni-plated region measured in a cross section perpendicular to the rolling surface of the base steel plate 11 is 0.2 to 4.0 μm. The Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 can be arranged on only one side of the base steel plate 11, or on both sides. Below, the Ni-plated steel plate 1 of this embodiment is described in detail.

[0045] (Base steel plate 11)

[0046] The base steel plate 11 is a steel plate serving as a base material of the Ni-plated steel plate 1. The composition, plate thickness, metal structure, etc. of the base steel plate 11 are not particularly limited. When the base steel plate 11 is used as a raw material for a battery container, for example, the base steel plate 11 is preferably made of low-carbon aluminum-killed steel and IF steel (Interstitial Free Steel / ultra-low carbon steel). In addition, when the base steel plate 11 is used as a raw material for a battery container, the thickness of the base steel plate 11 is preferably set to, for example, 0.15 to 0.8 mm.

[0047] (Fe-Ni diffusion alloy region 12)

[0048] The Fe-Ni diffusion alloy region 12 is a region obtained by mutual diffusion of Ni plating and the base steel plate 11. The Fe-Ni diffusion alloy region 12 can also be defined as a layer containing more than 5% by mass of Fe, and more than 90% by mass of the remaining part is Ni. As long as the above provisions are met, the Fe-Ni diffusion alloy region can also contain elements other than Fe and Ni (such as Co, etc.). In addition, the Fe-Ni diffusion alloy region is also allowed to contain impurities.

[0049] The thickness of the Fe-Ni diffusion alloy region 12 is not particularly limited and can be appropriately selected within a normal range. From the perspective of ensuring the film adhesion and corrosion resistance of the Ni-plated steel sheet 1, the thickness of the Fe-Ni diffusion alloy region is preferably 0.2 μm or more. On the other hand, from the perspective of ensuring the iron dissolution resistance of the Ni-plated steel sheet 1, the thickness of the Fe-Ni diffusion alloy region is preferably 1 μm or less.

[0050] (Ni-plated area 13)

[0051] The Ni-plated region 13 is a region in the Ni-plated region where no mutual diffusion with the base steel plate 11 occurs. The Ni-plated region 13 can also be defined as a layer containing less than 5% by mass of Fe, and more than 90% by mass of the remaining portion is Ni. In order to improve the mechanical properties of the Ni-plated region 13, the Ni-plated region 13 can also contain elements such as Co. The Ni-plated region becomes a soft recrystallized Ni layer due to annealing. The soft Ni-plated region follows the deformation of the steel plate during mechanical processing such as stamping and prevents the base steel plate 11 from being exposed. Therefore, the Ni-plated region 13 can further improve the processability of the Ni-plated steel plate 1.

[0052] In the Ni-plated steel plate 1 of the present embodiment, the equivalent circle diameter of the grains constituting the Ni-plated region 13 is within a predetermined range. Specifically, the average equivalent circle diameter of the grains composed of Ni(fcc) constituting the Ni-plated region 13 (hereinafter sometimes referred to as "Ni(fcc) grains") is within a range of 0.2 to 4.0 μm as measured in a cross section perpendicular to the rolled surface of the base steel plate 11. The so-called Ni(fcc) refers to a material containing less than 5% by mass of Fe, with 90% or more of the remainder being Ni, and having an fcc structure (lattice constant ) crystals. In addition, in the present embodiment, it should be noted that the average equivalent circular diameter of the Ni (fcc) grains is a value measured in the cross section. Because the crystals constituting the Ni-plated region of the Ni-plated steel plate are not equiaxed grains, the average equivalent circular diameter of the Ni (fcc) grains measured on the surface of the Ni-plated region may not be consistent with that measured in the cross section of the Ni-plated region. The Ni-plated steel plate 1 of the present embodiment is characterized in that the amount of grain boundaries in the interior is controlled rather than the amount of grain boundaries on the surface of the Ni-plated region. Therefore, the particle size of the Ni (fcc) grains of the Ni-plated steel plate 1 of the present embodiment should be evaluated in the cross section. Below, unless otherwise specified, the so-called average equivalent circular diameter means the average equivalent circular diameter measured in the cross section.

[0053] According to the experimental results of the present inventors, the average equivalent circle diameter of the Ni (fcc) grains constituting the Ni-plated area 13 can be set to 0.2 to 4.0 μm, thereby not damaging the formability of the Ni-plated steel sheet 1, and the Ni dissolution resistance can be dramatically improved. On the other hand, when the average equivalent circle diameter of the Ni (fcc) grains is less than 0.2 μm, the Ni dissolution resistance of the Ni-plated steel sheet is insufficient. In addition, when the average equivalent circle diameter of the Ni (fcc) grains is less than 0.2 μm, it is also conceivable that the electrodeposition becomes powdery and the processability deteriorates. On the other hand, when the average equivalent circle diameter of the Ni (fcc) grains exceeds 4.0 μm, wrinkles are easily generated in the Ni-plated area during drawing and thinning and stretching, thereby damaging the processability of the Ni-plated steel sheet. Therefore, the average equivalent circle diameter of the Ni (fcc) grains is set to 0.2 to 4.0 μm. The lower limit of the average equivalent circle diameter of the Ni(fcc) crystal grains may be 0.4 μm, 0.8 μm, 1.0 μm, or 1.5 μm, and the upper limit of the average equivalent circle diameter of the Ni(fcc) crystal grains may be 3.5 μm, 3.2 μm, 3.0 μm, or 2.5 μm.

[0054] The Ni-plated region 13 is not particularly limited as long as the above requirements are satisfied. However, the Ni-plated region 13 may further include the following features depending on the application of the Ni-plated steel sheet 1 .

[0055] In the Ni-plated steel sheet 1 of the present embodiment, the value obtained by dividing the average equivalent circle diameter of the Ni (fcc) grains of the Ni-plated region 13 by the thickness of the Ni-plated region 13 (hereinafter, sometimes referred to as "grain diameter-thickness ratio") is preferably 0.50 to 2.00. In addition, when the Ni (fcc) grains of the Ni-plated region 13 have a shape extending along the surface of the base steel plate 11, the equivalent circle diameter thereof may be larger than the thickness of the Ni-plated region 13. Therefore, there is a case where the grain diameter-thickness ratio exceeds 1.0.

[0056] By setting the particle size-thickness ratio to 0.50 or more, the Ni dissolution resistance of the Ni-plated steel sheet can be further improved. In addition, by setting the particle size-thickness ratio to 2.00 or less, the processability of the Ni-plated steel sheet 1 can be more stably ensured. For the above reasons, it is preferred to set the particle size-thickness ratio to 0.50 to 2.00. It is more preferred to set the particle size-thickness ratio to 0.70 or more, 0.90 or more, or 1.20 or more. In addition, it is more preferred to set the particle size-thickness ratio to 1.80 or less, 1.60 or less, or 1.50 or less.

[0057] The film thickness of the Ni-plated region 13 is not particularly limited, but from the perspective of ensuring the processability of the Ni-plated steel sheet 1, the thickness of the Ni-plated region is preferably 0.8 μm or more. It is also possible to set the thickness of the Ni-plated region to be 1.0 μm or more, 1.5 μm or more, or 2.0 μm or more. In addition, the processability improvement effect brought by the Ni-plated region is considered to be saturated when the thickness of the Ni-plated region exceeds about 6.8 μm. Therefore, from the perspective of economy, the thickness of the Ni-plated region is preferably 6.8 μm or less. It is also possible to set the thickness of the Ni-plated region to be 4.0 μm or less, 3.0 μm or less, or 2.0 μm or less.

[0058] The Ni deposition amount per single surface of the Fe—Ni diffusion alloy region 12 and the Ni plated region 13 may be set to 1.5 to 65 g / m 2 This is because the Ni deposition amount can be set to 1.5 g / m 2 The above is preferable because the corrosion resistance and iron dissolution resistance of the Ni-plated steel sheet 1 can be reliably ensured. 2 The amount of Ni deposited on each side may be set to 2.4 g / m 2 Above, 4.8g / m 2 Above or 8g / m 2 Alternatively, the Ni coating weight per single surface of the Ni-plated steel sheet 1 may be set to 32 g / m 2 Below, 24g / m 2 Below or 12g / m2 the following.

[0059] (Measurement method)

[0060] The method for determining the average equivalent circular diameter of the Ni(fcc) grains of the Ni-plated area 13 measured in a cross section perpendicular to the rolled surface of the base steel plate 11 is as follows. First, the Ni-plated steel plate 1 is resin-embedded and cut perpendicular to the rolled surface of the base steel plate 11. Next, the cut surface is mirror-polished. If necessary, a FIB (focused ion beam device) can also be used to prepare the cut surface. By performing EBSP (backscattered electron diffraction image analysis) on the cut surface, a Ni(fcc) image can be captured. By performing image processing on the Ni(fcc) image, the average area of ​​the Ni(fcc) grains in the EBSP image can be calculated based on the area of ​​each Ni(fcc) grain in the EBSP image and the area ratio of each Ni(fcc) grain in the image. Based on the average area, the average equivalent circular diameter of the Ni(fcc) grains can be calculated. The calculation of the average equivalent circular diameter of the Ni(fcc) grains is based on the observation field area of ​​300μm from the Ni-plated area. 2 The image processing is performed on the image of 10 μm×30 μm or more.

[0061] exist Picture 3 , an example of a Ni(fcc) image obtained using EBSP is shown. Picture 3 The photo is a grayscale image, but in the actual EBSP image, the orientation of the grains is displayed by color. The position where the crystal orientation difference of 5° or more is formed is judged as the grain boundary, and the area surrounded by the grain boundary is judged as the Ni(fcc) grain. However, when the average equivalent circle diameter of the Ni(fcc) grain is less than 0.05μm, it is regarded as noise and ignored.

[0062] The thickness of the Ni-plated region 13 can be measured by performing a depth analysis of the element concentration using EPMA or the like. By grinding the cut surface of the Ni-plated steel plate 1 perpendicular to the rolled surface of the base steel plate 11 and continuously analyzing the components from the surface of the Ni-plated steel plate 1 to the base steel plate 11, it is possible to distinguish between a region where the Fe content is 5% or more and more than 90% of the remainder is Ni (i.e., the Fe-Ni diffusion alloy region 12), a region where the Fe content is less than 5% and more than 90% of the remainder is Ni (i.e., the Ni-plated region 13), and regions other than the region (i.e., the base steel plate 11). Based on the results of the discrimination, the interfaces of the base steel plate 11, the Fe-Ni diffusion alloy region 12, and the Ni-plated region 13 can be determined. By measuring the distance between the interfaces, the thickness of the Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 can be measured. In consideration of variations, it is preferred that the above-mentioned measurement be performed at five locations, and the average value of the measured values ​​at the respective locations be regarded as the thickness of the Fe—Ni diffusion alloy region 12 and the Ni plated region 13 .

[0063] The amount of Ni deposited can be measured, for example, by ICP analysis. First, the Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 of a predetermined area are dissolved with acid. Next, the total amount of Ni contained in the solution is quantitatively analyzed by ICP. By dividing the total amount of Ni determined by ICP by the predetermined area, the amount of Ni deposited per unit area can be obtained.

[0064] (Manufacturing method)

[0065] Next, a preferred method for producing the Ni-plated steel sheet 1 of the present embodiment will be described. However, the Ni-plated steel sheet having the above-mentioned requirements is regarded as the Ni-plated steel sheet 1 of the present embodiment regardless of the production method.

[0066] The method for manufacturing the Ni-plated steel sheet 1 of the present embodiment includes a step of electroplating Ni on a base steel sheet 11 to obtain a base Ni-plated steel sheet, and a step of annealing the base Ni-plated steel sheet. The Ni-plating step includes three or more power-on periods and rest periods between the power-on periods, and the average current density per single surface of the base steel sheet during each power-on period is set to 200 A / m 2 ~3500A / m 2 The amount of current applied to each side of the base steel plate during each current application period was set to 800 C / m 2 ~40000C / m 2In each power-on period, the current density is set to be non-constant, and the maximum current density per single side of the base steel plate is set to be 7% or more higher than the average current density per single side of the base steel plate. In addition, the soaking temperature in annealing is set to be 650°C to 850°C, and the soaking time in annealing is set to be 10 seconds to 109 seconds.

[0067] (Ni electroplating process)

[0068] In the method for manufacturing the Ni-plated steel sheet 1 of the present embodiment, first, a base steel sheet having unalloyed Ni plating (base Ni-plated steel sheet) is produced by electroplating Ni on the base steel sheet 11. In this process, the current conduction pattern should satisfy the following requirements.

[0069] (1) It includes three or more energization periods and rest periods between these energization periods.

[0070] (2) The average current density I during each power-on period ave Set to 200~3500A / m 2 .

[0071] (3) The amount of current applied during each current application period is set to 800 to 40,000 C / m 2 .

[0072] (4) Let the maximum current density I during each energization period be max The average current density I during the power-on period ave More than 7% larger.

[0073] The power-on pattern includes three or more power-on periods and rest periods between these power-on periods. The so-called power-on period refers to the period during which current flows through the base steel plate 11, and the so-called rest period means the period during which the power supply to the base steel plate 11 is substantially stopped. In addition, ideally, the current value should be 0 during the rest period, but due to the performance of the power supply and the plating device, sometimes even if the power supply is stopped, it takes a certain amount of time before the current value is completely 0. Therefore, during the period when the current flowing through the base steel plate 11 is small (for example, the current density is less than I ave In the case where it is difficult to make the current density completely zero due to the constraints of the manufacturing equipment, the rest period can also be regarded as the period when the current density is less than I ave 5% of the period, and the power-on period is regarded as the period other than that. ave Under different circumstances, the current density can be less than the minimum I ave The period of 5% of the total period of employment is deemed to be a period of rest.

[0074] According to the experimental results of the present inventors, the Ni-plated steel sheet 1 of the present embodiment cannot be obtained when the number of energization periods is 2 or less. This is considered to be because periodic internal stress changes in the depth direction cannot be imparted to the Ni plating before annealing.

[0075] The average current density I during each power-on period ave Set to 200~3500A / m 2 The current flow during each power-on period is set to 800 to 40000 C / m 2 . Assume that the maximum current density I during each power-on period is max The average current density I during the power-on period ave The average current density I ave , refers to the value obtained by integrating the graph of current density and time within the power-on period defined above (equivalent to the area of ​​the shaded portion in Figures 1-1 to 1-3) by the length of the power-on period. The so-called power supply refers to the power supply during the power-on period defined above. The so-called maximum current density I max , refers to the maximum value of the current density during each power-on period.

[0076] At the average current density I ave In the case of insufficient current, or at the maximum current density I max If the average current density is insufficient, the Ni-plated steel sheet 1 of the present embodiment cannot be obtained. This is presumed to be because the change in internal stress given to the Ni plating before annealing becomes small. ave , current flow or maximum current density I max In case of excess (e.g. in I max More than 4000A / m 2 In the case of ), Ni plating cannot be formed normally due to burns on the plating surface.

[0077] An example of the energization pattern is shown in FIG1-1. Here, the current density at the start time point of the energization period is set to the maximum current density I max On the other hand, as shown in FIG1-2, the current density at the start time of the power-on period is set to the minimum current density, the current density is gradually increased, and the current density at the end time of the power-on period is set to the maximum current density I max . In addition, as shown in FIG. 1-3 , the current density may be gradually decreased and the current density may be gradually increased alternately. Although not shown in the figure, the current density may be set to the maximum current density I in the middle of the current-carrying period. maxIn addition, although the average current density, the maximum current density, and the amount of electricity are consistent between each power-on period in FIG. 1-1 to FIG. 1-3, these values ​​may be different for each power-on period as long as the above provisions can be met in each power-on period.

[0078] During the rest period, the current density can be set to 0 or set to a value lower than the maximum current density I ave A sufficiently low value (e.g. less than I ave The length of the idle period is not particularly limited, but may be set to be not less than 0.1 seconds and not more than 10 seconds in consideration of power supply capability and the like.

[0079] (Annealing process)

[0080] In the manufacturing method of the Ni-plated steel sheet 1 of the present embodiment, a part of the Ni plating is then alloyed by annealing the raw material Ni-plated steel sheet. The soaking temperature in the annealing is set to be 650° C. to 850° C., and the soaking time in the annealing is set to be 10 seconds to 109 seconds. In addition, the soaking time means the time for isothermal holding from the time when the temperature of the raw material Ni-plated steel sheet reaches the soaking temperature of 650° C. to 850° C.

[0081] When the soaking temperature or soaking time is insufficient, alloying is insufficient and recrystallization is insufficient in the Ni-plated region 13. As a result, the Ni-plated steel sheet 1 of the present embodiment cannot be obtained. On the other hand, when the soaking temperature or soaking time is excessive, all the Ni plating is alloyed, so there is a risk that the Ni-plated region 13 will disappear.

[0082] [Example]

[0083] The effects of one embodiment of the present invention are described in more detail by way of examples. However, the conditions in the examples are only one conditional example adopted to confirm the feasibility and effect of the present invention. The present invention is not limited to this one conditional example. As long as the purpose of the present invention is achieved without departing from the gist of the present invention, various conditions can be adopted.

[0084] Various Ni-plated steel sheets were produced under the conditions described below.

[0085] The base steel plate was Al-K steel (C: 0.057 mass %, Si: 0.004 mass %, Mn: 0.29 mass %, P: 0.014 mass %, and S: 0.007 mass %. The remainder was iron and impurities). The plate thickness was 0.3 mm.

[0086] The base steel plate 11 was electroplated with Ni in a Watt bath (bath composition: 240 g / L nickel sulfate hexahydrate, 30 g / L nickel chloride hexahydrate and 30 g / L boric acid. pH: 3.5. Bath temperature: 45°C) under the conditions shown in Table 1, and then annealed under the conditions shown in Table 1.

[0087]

Table 1

[0088]

[0089] In addition, other conditions not shown in Table 1 are as follows. The shape of the current pattern is the shape shown in Figures 1-3. That is, in the odd-numbered energizations, the current density is gradually reduced, and in the even-numbered energizations, the current density is gradually increased. ave , current consumption and I max It is a common value in each power-on period. The length of the rest period is 0.1 second. The annealing atmosphere is N2-2% H2. It is confirmed that the sheet temperature is 300°C or less after cooling from the soaking temperature in the furnace atmosphere gas, and then the sheet is taken out of the furnace.

[0090] The various Ni-plated steel sheets obtained by the above-mentioned means were evaluated by the following means. The evaluation results are shown in Table 4.

[0091] (1) Measurement of the average equivalent circle diameter of Ni (fcc) grains in the Ni-plated area measured in a cross section perpendicular to the rolled surface of the base steel plate (Ni (fcc) equivalent circle diameter)

[0092] First, the Ni-plated steel plate 1 is embedded in resin and cut perpendicular to the rolled surface of the base steel plate 11. Next, the cut surface is mirror-polished. By performing EBSP (backscattered electron diffraction image analysis) on the cut surface, a Ni(fcc) image is captured. By performing image processing on the Ni(fcc) image, the average area of ​​the Ni(fcc) grains in the EBSP image is calculated based on the area of ​​each Ni(fcc) grain in the EBSP image and the area ratio of each Ni(fcc) grain in the image. Based on the average area, the average equivalent circular diameter of the Ni(fcc) grains is calculated. The observation field area at this time is 300μm 2 (10μm×30μm).

[0093] In addition, for reference, the average equivalent circular diameter of Ni (fcc) grains in the Ni-plated area was measured on the surface of the Ni-plated area for samples that were evaluated as qualified. The measurement method is as follows. First, the Ni-plated steel plate 1 was cleaned with acetone. Then, the surface of the Ni-plated area was ion milled (Hitachi High-Technology ion milling device ArBlade5000 uses gas: Ar, accelerating voltage: 4kV, sputtering time: 4 minutes). For the surface obtained in this way, EBSP was implemented in the same order as the cross-section evaluation, and the average equivalent circular diameter of the Ni (fcc) grains was calculated.

[0094] (2) Measurement of the Thickness of the Fe-Ni Diffusion Alloy Region 12 and the Ni Plated Region 13

[0095] The thickness of the Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 is measured by performing a depth analysis of the element concentration using EPMA. By grinding the cut surface of the Ni-plated steel plate 1 perpendicular to the rolled surface of the base steel plate 11 and continuously analyzing the components from the surface of the Ni-plated steel plate 1 to the base steel plate 11, the region where the Fe content is more than 5% and more than 90% of the remaining part is Ni (i.e., the Fe-Ni diffusion alloy region 12), the region where the Fe content is less than 5% and more than 90% of the remaining part is Ni (i.e., the Ni-plated region 13), and the region other than the region (i.e., the base steel plate 11) are distinguished. Based on the results of the discrimination, the interfaces of the base steel plate 11, the Fe-Ni diffusion alloy region 12, and the Ni-plated region 13 are determined. The thickness of the Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 is measured by measuring the distance between the interfaces. The above-mentioned measurement was performed at five locations in consideration of variations, and the average value of the measured values ​​at the respective locations was regarded as the thickness of the Fe—Ni diffusion alloy region 12 and the Ni plated region 13 .

[0096] (3) Measurement of the value obtained by dividing the average equivalent circle diameter of the Ni (fcc) grains in the Ni-plated region by the thickness of the Ni-plated region (grain diameter-thickness ratio)

[0097] The grain size-thickness ratio is obtained by dividing the average equivalent circle diameter obtained in the procedure of (1) above by the thickness of the Ni-plated region 13 obtained in the procedure of (2) above.

[0098] (4) Measurement of Ni adhesion amount

[0099] The amount of Ni deposited on the Ni-plated steel sheet 1 was measured by ICP analysis. 2The Fe-Ni diffusion alloy region 12 and the Ni-plated region 13 (50 mm square) are dissolved. Then, the total Ni content contained in the solution is quantitatively analyzed by ICP. The total Ni content quantitatively determined by ICP is divided by the area of ​​the above-mentioned measurement target region to obtain the Ni deposition amount per unit area.

[0100] (5) Evaluation of processability

[0101] A 4-stage multi-station press was used for processing. The final shape of the test piece was a cylindrical can with a diameter of 18 mm and a height of 50 mm. A 10 mm square area centered at a height of 25 mm was cut out, and secondary electron images of the inner surface of the can were taken with a SEM at a magnification of 200 times in three fields of view. 2 The number of Ni-based film peeling and cracks in the area above 1 mm was measured. 2 When 10 or more cracks were observed in total, it was indicated as "B (bad)" in the table. 2 When the total is 1 to 9 or less, it is indicated as "G (good)" in the table, and when it is 0, it is indicated as "VG (very good)" in the table. In addition, when wrinkles are visible during punching, they are also indicated as "B (poor)" in the table.

[0102] (6) Evaluation of Ni dissolution resistance

[0103] 10 mL of 35% KOH solution was sealed in the inner surface of the cylindrical can made for the evaluation of processability, and a platinum wire was set as a counter electrode in the center of the inner surface of the cylindrical can. The potential of the cylindrical can was maintained at 0.3 V vs. Hg / HgO with a Hg / HgO reference electrode, and a constant potential corrosion test was performed at 60°C for 1000 hours. The KOH solution after the test was analyzed by ICP-MS, and the Ni and Fe dissolved into the solution were quantified. Regarding the evaluation criteria, first, when Fe is detected to be above 0.1 mg / L, it is displayed as "B (poor)" in the table regardless of the amount of Ni dissolved. In addition, even if Fe is not detected (less than 0.1 mg / L), when Ni is detected to be more than 5 mg / L, it is also displayed as "B (poor)" in the table. In the table, when no Fe was detected (less than 0.1 mg / L) and Ni was 1-5 mg / L, it was displayed as “G (good)”, when no Fe was detected (less than 0.1 mg / L) and Ni was 0.1-1 mg / L, it was displayed as “VG (very good)”, and when no Fe was detected (less than 0.1 mg / L) and Ni was also less than 0.1 mg / L, it was displayed as “GG (very good)”.

[0104]

Table 2

[0105]

[0106]

Table 3

[0107] Actual performance issue Processability Ni elution resistance A1 G V.G. A2 V.G. GG A3 V.G. GG A4 V.G. GG A5 V.G. GG A6 G V.G. A7 V.G. G A8 V.G. V.G. A9 V.G. GG A10 V.G. GG A11 V.G. GG A12 V.G. GG A13 V.G. V.G. A14 V.G. GG A15 V.G. GG A16 V.G. GG A17 V.G. GG A18 V.G. V.G. A19 V.G. V.G. A20 V.G. GG A21 V.G. V.G. A22 G G A23 V.G. V.G. A24 V.G. V.G. A25 V.G. V.G. A26 G V.G. A27 V.G. V.G. A28 V.G. V.G. A29 V.G. V.G. A30 V.G. V.G. A31 V.G. V.G. A32 G G A33 V.G. G A34 V.G. G A35 V.G. V.G. A36 V.G. V.G. A37 V.G. GG A38 V.G. GG A39 G GG B1 B G B2 B G B3 B B B4 G B B5 B V.G. B6 B G B7 B B B8 B B B9 B B B10 B B B11 G B

[0108] As shown in Table 2, in all Examples, the average equivalent circle diameter of Ni (fcc) grains in the Ni-plated region measured in a cross section perpendicular to the rolled surface of the base steel plate was 0.2 to 4.0 μm. Furthermore, these Examples were excellent in workability and Ni dissolution resistance.

[0109] In addition, in these examples, no particular correlation was found between the average equivalent circular diameter of the Ni(fcc) crystal grains measured in the cross section and the average equivalent circular diameter of the Ni(fcc) crystal grains measured from the surface. Therefore, it is considered that the average equivalent circular diameter of the Ni(fcc) crystal grains measured in the cross section cannot be estimated based on the average equivalent circular diameter of the Ni(fcc) crystal grains measured from the surface.

[0110] On the other hand, in Comparative Examples B1 to B6, the average equivalent circle diameter of Ni (fcc) crystal grains was outside the range of the present invention. Regarding these Comparative Examples, one or both of the workability and the Ni dissolution resistance were inferior to those of the Examples.

[0111] Comparative Example B1 is an example in which the number of times of energization is only 2. In this Comparative Example B1, Ni (fcc particles) exceeds 4.0 μm, and the processability is poor.

[0112] Comparative Example B2 is 1 ave Insufficient example: In Comparative Example B2, the Ni (fcc particles) exceeded 4.0 μm and the workability was poor.

[0113] Comparative Example B3 is 1 ave In this comparative example B3, the Ni (fcc particles) was smaller than 0.2 μm, and the processability and Ni dissolution resistance were poor.

[0114] Comparative Example B4 is an example of insufficient current flow. In this Comparative Example B4, no Ni region remains, and the measurement of Ni (fcc particles) cannot be performed. In terms of performance, the resistance to Ni and Fe dissolution is poor.

[0115] Comparative Example B5 is an example in which the amount of energization exceeded 100 Å. In Comparative Example B5, the Ni (fcc particles) exceeded 4.0 μm, and the workability was poor.

[0116] Comparative Example B6 is 1 max In this comparative example B6, I max For I ave 103% of Ni (fcc particles) exceeds 4.0μm and the processability is poor.

[0117] Comparative Example B7 is 1 max In this comparative example B7, I max More than 4000A / m 2 , so it becomes a plating burn appearance, and the processability and Ni dissolution resistance are poor.

[0118] Comparative Examples B8 to 11 are examples where the annealing conditions are inappropriate. In Comparative Examples B8 to 11, the Ni (fcc particles) are smaller than 0.2 μm, and both the processability and the Ni dissolution resistance are poor, or the processability is poor.

[0119] Industrial Availability

[0120] According to the present invention, a Ni-plated steel sheet having the formability required for a steel sheet for a battery and excellent Ni dissolution resistance and a method for producing the same can be provided. Such a Ni-plated steel sheet is preferred as a steel sheet for a battery and therefore has extremely high industrial applicability.

[0121] Description of Reference Numerals

[0122] 1 Ni-plated steel sheet

[0123] 11. Base steel plate

[0124] 12 Fe-Ni diffusion alloy area

[0125] 13 Ni plating area

Claims

1. A Ni-plated steel sheet, characterized in that: include: Base steel plate, The Fe-Ni diffusion alloy region is arranged on the base steel plate, and A Ni-plated region, which is disposed on the Fe-Ni diffusion alloy region; The average equivalent circle diameter of the crystal grains composed of Ni-fcc in the Ni-plated region measured in a cross section perpendicular to the rolled surface of the base steel plate is 0.2 to 4.0 μm, No coating surface burns, The Ni-fcc refers to a material containing less than 5 mass % of Fe, with 90 mass % or more of the remainder being Ni, and having a lattice constant Crystallization of the fcc structure.

2. The Ni-plated steel sheet according to claim 1, wherein A value obtained by dividing the average equivalent circle diameter of the crystal grains composed of the Ni-fcc in the Ni plated region by the thickness of the Ni plated region is 0.50 to 2.

00.

3. The Ni-plated steel sheet according to claim 1 or 2, characterized in that: The Ni deposition amount per single surface in the Fe-Ni diffusion alloy region and the Ni plating region is 1.5 to 65 g / m 2 .

4. The method for producing a Ni-plated steel sheet according to any one of claims 1 to 3, wherein: include: A process of electroplating Ni on a base steel sheet to obtain a raw material Ni-plated steel sheet, and A step of annealing the raw material Ni-plated steel sheet; The Ni electroplating includes three or more power-on periods and rest periods between the power-on periods; The average current density per single surface of the base steel plate during each of the energization periods was set to 200 A / m 2 ~3500A / m 2 ; The amount of electricity applied to each single surface of the base steel plate during each of the electricity application periods was set to 800 C / m 2 ~40000C / m 2 ; During the energization period, the current density is set to be non-constant, and the maximum current density per the single side of the base steel plate is set to be 7% or more higher than the average current density per the single side of the base steel plate, and 4000 A / m 2 the following; The soaking temperature in the annealing is set to be 650° C. or higher and 850° C. or lower; The soaking time in the annealing is set to be not less than 10 seconds and not more than 109 seconds.

5. The method for producing a Ni-plated steel sheet according to claim 4, wherein: The length of each of the rest periods is 0.1 seconds or longer.

Citation Information

Patent Citations

  • Nickel plating steel strip with high corrosion resistance and its production

    JP1994002104A

  • Nickel-plated steel sheet and process for producing battery can using the nickel-plated steel sheet

    WO2010143374A1

  • Ni-plated steel sheet for battery can having excellent pressability

    WO2011024443A1

  • Ni-plated steel sheet with excellent pressability for battery can

    WO2011083562A1

  • Surface-treated steel plate for cell container

    WO2017094919A1